The Whitish Inner Mantle of the Giant Clam, Tridacna squamosa, Expresses an Apical Plasma Membrane Ca2+-ATPase (PMCA) Which Displays Light-Dependent Gene and Protein Expressions - Ip, Yuen K.; Hiong, Kum C.; Goh, Enan J. K.; Boo, Mel V.; Choo, Celine Y. L.; Ching, Biyun; Wong, Wai P.; Chew, Shit F. (Frontiers in Physiology, 2017)
Giant clams live in symbiosis with extracellular zooxanthellae and display high rates of growth and shell formation (calcification) in light. Light-enhanced calcification requires an increase in the supply of Ca2+ to, and simultaneously an augmented removal of H+ from, the extrapallial fluid where shell formation occurs. We have obtained the complete coding cDNA sequence of Plasma Membrane Ca2+-ATPase (PMCA) from the thin and whitish inner mantle, which is in touch with the extrapallial fluid, of the giant clam Tridacna squamosa. The deduced PMCA sequence consisted of an apical targeting element. Immunofluorescence microscopy confirmed that PMCA had an apical localization in the shell-facing epithelium of the inner mantle, whereby it can actively secrete Ca2+ in exchange for H+. More importantly, the apical PMCA-immunofluorescence of the shell-facing epithelium of the inner mantle increased significantly after 12 h of exposure to light. The transcript and protein levels of PMCA/PMCA also increased significantly in the inner mantle after 6 or 12 h of light exposure. These results offer insights into a light-dependable mechanism of shell formation in T. squamosa and a novel explanation of light-enhanced calcification in general. As the inner mantle normally lacks light sensitive pigments, our results support a previous proposition that symbiotic zooxanthellae, particularly those in the colorful and extensible outer mantle, may act as light-sensing elements for the host clam.